Imbalanced initial populations between dark and bright states in semiconductor quantum dots - Lin, Sheng-Di; Fu, Ying-Jhe; Cheng, Chun (My University, 2012)
We present the observation and analysis of long-lived exciton in individual InAs quantum dots (QDs). The general model considering the interplay between dark and bright states reveals the two key factors responsible for the long decay time: the shortened spin-flip time at elevated temperature and the imbalanced initial populations between the dark and bright states. The later one plays a key role in the unusual phenomena and leads to the possibility of spin-dependent relaxation process in QDs. (C) 2012 Optical Society of America